Development of Rice Integrated Cattle Business in Semangga District, Merauke Regency - Abdul Rizal; Adrianus Adrianus; Nurliah Nurliah (Pascasarjana Universitas Sulawesi Tenggara, 2022)
This study aims to provide information on the strategy of developing beef cattle business integrated with rice plants. The method used is a survey method with a Stratified Random Sampling sampling technique. The consideration in determining this location is because the majority of the people are farmers and breeders, namely rice farmers and cattle breeders with the research population being all cattle farmers who also carry out rice farming. The data sources used were primary and secondary data which were analyzed using SWOT analysis. The conclusion from the research is that the business developed is in the quadrant 1 category which means Aggressive with a value of (6.5). The strategy is to utilize human resources to assist the marketing process, utilize available land to increase production and maximize business by utilizing facilities and infrastructure.